ANÁLISIS BAYESIANO EN PRESENCIA DE COVARIABLES PARA DATOS DE SOBREVIVENCIA MULTIVARIADOS: UN EJEMPLO DE APLICACIÓN - Santos, Carlos Aparecido; Achcar, Jorge Alberto (Revista Colombiana de Estadística, 2011)
In this paper, we introduce a Bayesian analysis for survival multivariate data in the presence of a covariate vector and censored observations. Different “frailties” or latent variables are considered to capture the correlation among the survival times for the same individual. We assumeWeibull or generalized Gamma distributions considering right censored lifetime data. We develop the Bayesian analysis using Markov Chain Monte Carlo (MCMC) methods.